Tinjauan Sistematis: Kompetensi Profesional Guru terhadap Efektivitas Pembelajaran dan Kinerja dalam Kurikulum Merdeka - Nur Khadijah Shabrina Putri Suryodiningrat; Sabrina Nabilah; Suci Artika Putri Utami; Sefti Ayu Rahmadani; Mila Aristia Dewari; Sri Lestari Handayani (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This systematic review examines the influence of teachers' professional competence on learning effectiveness and performance in the implementation of Merdeka Curriculum. The research uses the Systematic Literature Review (SLR) method with descriptive qualitative approach, analyzing 42 scientific articles published between 2020-2025 from Google Scholar, Garuda Portal, DOAJ, and Scopus databases, selected through systematic screening from an initial pool of 87 articles following PRISMA guidelines. The inclusion criteria include national and international journals discussing professional competence, learning effectiveness, teacher performance, and Merdeka Curriculum. Data analysis was performed through content analysis and thematic synthesis. The results show that teachers' professional competence significantly affects learning effectiveness and teacher performance in Merdeka Curriculum implementation. Professional competence encompasses mastery of subject matter, teaching skills, use of technology, assessment abilities, and continuous professional development. Teachers with high professional competence demonstrate better performance in designing differentiated learning, implementing project-based learning, and developing innovative teaching materials. This study concludes that strengthening teachers' professional competence through structured training programs, mentoring, and professional learning communities is essential to optimize Merdeka Curriculum implementation and improve the quality of national education.